Trace elements levels in growing camels’ (Camelus dromedarius) biological tissues from semi-arid areas - Mutassim M. Abdelrahman; Ibrahim A. Alhidary; Mohsen M. Alobre; Abdulkareem M. Matar; Mohammed A. Al-Badwi; Mohammed M. Qaid; Riyadh S. Aljumaah (Journal of Applied Animal Research)
This study focused on the variation of copper (Cu), zinc (Zn), manganese (Mn), selenium (Se), iron (Fe), and iodine (I) concentrations in whole blood, rumen fluid, and tissues of slaughtered growing camels (>one-year-old) raised in five regions of Saudi Arabia in spring. One hundred and forty-three samples were collected and wet digested to analyze the concentrations of Cu, Zn, Mn, Se, Fe, and I by Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). Results showed significant (P < 0.05) variations among the five regions for camels’ liver Cu, Zn, Se, Mn, and I levels, while Fe concentration did not differ. In contrast to liver Fe, liver Se levels in all regions were lower than suggested (recommended ranges of liver Se and Fe: 0.272–0.921 and 28–51 ug/g). Levels for Cu, Zn, Se, Mn, and Fe in meat tissues differed significantly in the five regions. For rumen fluid samples, Mn levels were higher in the eastern region (P < 0.05) than the central region, and vice versa for I levels. In conclusion, Cu, Zn, Mn, and Se concentrations varied by location during the spring. In addition, rumen fluid correlated positively with meat for Fe and liver for I, but negatively with rumen tissue for Se and Zn.